2021
DOI: 10.1093/europace/euaa400
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the cause of conduction delays in patients with repaired Tetralogy of Fallot

Abstract: Aims Cardiac dyssynchrony in patients with repaired Tetralogy of Fallot (rToF) has been attributed to right bundle branch block (RBBB), fibrosis and/or the patches that are inserted during repair surgery. We aimed to investigate the basis of abnormal activation in rToF patients by mapping the electrical activation sequence during sinus rhythm (SR) and right ventricular (RV) pacing. Methods and Results A total of 17 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…RBBB is uncommon prior to primary repair in TOF occurring only in 4% of cases but increases significantly following primary repair to 61% ( p = <0.001) and increases subsequently through the early postoperative period after PVR (89%). Horowitz et al showed that RBBB is related to infundibular resection in rTOF and more recently Verzaal et al showed that the main mechanism is block in the Purkinje system ( 40 , 41 ). Of interest, RBBB increases after PVR, which could be due to the need to excise additional muscle to accommodate the conduit.…”
Section: Discussionmentioning
confidence: 99%
“…RBBB is uncommon prior to primary repair in TOF occurring only in 4% of cases but increases significantly following primary repair to 61% ( p = <0.001) and increases subsequently through the early postoperative period after PVR (89%). Horowitz et al showed that RBBB is related to infundibular resection in rTOF and more recently Verzaal et al showed that the main mechanism is block in the Purkinje system ( 40 , 41 ). Of interest, RBBB increases after PVR, which could be due to the need to excise additional muscle to accommodate the conduit.…”
Section: Discussionmentioning
confidence: 99%
“… 12 However, local slow conduction at the septal infundibulum between the VSD patch and the pulmonary annulus (SCAI 3) significantly alters the terminal activation of the RV, with a shift in the activation wavefront from the basal lateral peri-tricuspid RV towards the lateral RVOT ( Figure 5 ), provided that there is no normal conducting AI 4. 12 , 13 The latter is observed in only a small group of rTOF patients with a muscular ridge between the VSD patch and the tricuspid annulus, information that is usually available from the surgical reports. In these patients, rapid conduction through AI 4 will compensate for the delay through AI 3 and will result in normal terminal RV activation ( Figure 7A ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data, though, has demonstrated that the more distal right sided conduction system is relatively intact. (Verzaal et al, 2021).…”
Section: Future Directionsmentioning
confidence: 99%